The role of wage subsidies in the Macedonian labour market - Dimitar Nikoloski (CES Working Papers, 2023)
The main rationale for wage subsidies is giving job opportunities to workers who would otherwise remain unemployed or take jobs that do not exploit their potential productivity. The aim of this paper is to evaluate the wage subsidy programme in North Macedonia for the period 2018-2019 in order to provide a sound basis for its redesign in the times of Covid-19 crisis. The Propensity score matching is used as a principal estimation method. Moreover, we further explore the impact of the wage subsidies on the outcome variables for particular disadvantaged segments by disaggregation of the average treatment effect on treated individuals. The evaluation reveals improvement of the wage subsidy program in 2019 relative to 2018. However, having in mind the impact of the Covid-19 pandemics, there is a room for redesign of this measure by improving its targeting and conditions for retaining the subsidised jobs in the long run.
Keywords: 330; wage subsidy; labour market; unemployment; COVID-19